Strategic system effects in resort and tourist spheres - Zakharchenko, Pavel; Kostenko, Ganna; Kungurtseva-Mashchenko, Tatyana (Kyiv National University of Trade and Economics, 2020)
In modern world economy the resort recreations are one of the most highprofitable spheres of managing. Ukraine owns the powerful resort and tourist potential, which effective development can bring a real economic benefit. The market environment needs are in the form of demand and ways to meet them mediated by the market in the form of structural shifts. They are important for forecasting of behavior of the market of resort and tourist products. One of the results of economic transformation in the resort economy is a transition to a new development strategy that is the transition from a seller’s market to a buyer’s market. It, in turn, generates numerous system transformational effects to which number, except transformational crisis, follow to carry and transformational structural shifts. Thus, it is possible to speak about difficult system of transformational effects among which there are as effects, which specifics consist only in quantitative differences of transformational economy from market, and effects, which provide existence of qualitative differences between them. In research, set of indicators, which allow analysing structural shifts in resort-recreation economy upon transition to new strategy of development, is constructed. The structure of system is considered, as set of proportions between elements. The movement of all system is described by the reduced indexes of volumes, and the relative movement of production of resort-recreation products in system – is described by indicators of structural shifts. Expected calculations are executed and scenarios developments of Priazovye resort-recreation complex are gained.
Keywords: resort and tourist sphere; economic transformations; strategic system effects; structural shifts; set of indicators